Electrochemically synthesized 2 H-MoS2/sulfur-doped graphene composite at room temperature with superior lithium storage performance - Sahin, Aysu S.; Hacinecipoglu, Ayse V.; Al-Bujasim, Mohammed; Gencten, Metin; Sahin, Yucel (SPRINGER HEIDELBERG, 2026)
This study introduces a novel room-temperature electrochemical synthesis method for composite anode materials made of 2 H-Molybdenum Disulfide (MoS2) and sulfur-doped graphene powders (S-GP) for lithium-ion batteries (LIBs). The composite leverages MoS2's high lithium storage capacity and the electrical conductivity of sulfur-doped graphene for enhanced performance. Structural characterization using Raman spectroscopy, XPS, XRD, SEM, and TEM confirms successful synthesis and a unique composite structure. Electrochemical tests show an initial capacity of 1433 mAh/g at 0.1 C, with good recovery at higher C-rates, indicating excellent rate capability and cycling stability. Extended cycling tests demonstrate that the material retains similar to 248 mAh/g at 10 C, with over 90% Coulombic efficiency for more than 100 cycles. This scalable, environmentally friendly synthesis method provides a promising path for next-generation energy storage. The findings highlight the potential of MoS2 and sulfur-doped graphene as high-performance anode materials, improving energy density and long-term stability in LIBs.
Keywords: Lithium-ion battery; Anode material; 2-dimensional material; Molybdenum disulfide; S-doped graphene; DOPED GRAPHENE; ANODE MATERIALS; MULTILAYER GRAPHENE; ELECTRODE MATERIALS; CYCLIC VOLTAMMETRY; RAMAN-SPECTROSCOPY; ION; MOS2; GRAPHITE; BATTERY; Chemistry; Electrochemistry; Physics